RELATIONSHIPS PARENTING KNOWLEDGE ABOUT MOTHER WITH CHILDREN IN DEVELOPMENT GROUP fine motor PLAY TK ISLAM AL PLUS IKHLASH YOGYAKARTA - Pratiwi .; Slamet Widodo; Mustain . (STIKES DUTAGAMA KLATEN, 2012)
Background: There is no parent who deliberately and consciously provide education and guidance to their children so that their children have failed in life. Even in principle, aspiring parents and children are always trying to succeed in later life, however, not infrequently the parents (perhaps because the level of education or lack full awareness in educating) a failure in the context of the child's personality formation. Both the poor child is closely associated with the care and education provided by parents.Objective: This study aims to determine the relationship of maternal knowledge about parenting children with fine motor development.Research method: This type of observational analytic study with cross sectional research design. Population was all mothers and children who are in kindergarten Playgroup Plus Al Ikhlas Islamic. Sampling techniques in total sampling with sample size 34 people. Measurement of age, education, occupation, sex obtained with a list of questions or questionnaires. While the fine motor skills using the observation made by DDST II. Data processing using a computer with a univariate analysis, bivariate, Pearson and spearman's rank. Results: The results of the study is the age of majority 26-30tahun mother 17 people (50%), education elementary school a majority of 13 people (38.2%), the majority of jobs do not work 10 people (29.4%). Majority of children age 4-6tahun 28 people (82.4%) and a majority of 19 were female (55.9%). Knowledge of mothers about good parenting category 4 people (11.8%), category quite 23 people (67.6%), category of less than 7 persons (20.6%). For fine motor development of children category pass / good 26 people (76.5%), a category not good lulus.tidak 8 people (23.5%). Thus, proving that the knowledge of mothers about parenting has a significant relationship with the child's fine motor development.Conclusion: The better the knowledge of mothers about parenting will impact on both child development fine motor by 44.5%. From the research results suggested that maternal knowledge about parenting improved fine motor development of children to be good.